A New Mixed Method to Select Non-Linear Complex Time Series - Pedro Ferreira; Mendes, D. A. (3rd International Conference on Dynamics, Games and Science, 2014)
Implementation of a new mixed method to select non-linear complex financial series (fossil energetic commodities, carbon allowances commodity, and European eolic main-building utilities), underlying the local constant models on the attractors (Small and Tse (2004)) and the maximum likelihood estimates of fractals (Takens (1985)), for successive embedding dimensions (starts at one). The time series of the asset daily prices (contracts (2000-2008)) such as coal, Acciona, Gamesa, and Repower present optimal embedding dimensions (5 ? de < 10) featuring non-linear complex (chaos and noise) financial series.